Benign skin diseases affecting the vulva. Issue 9 (September 2019) - Kirby, Lisa; Simpson, Rosalind; Nunns, David
Abstract: Vulval skin disease is common in gynaecological practice. This review aims to enhance clinical skills in patient assessment, vulval examination and treatment of common benign vulval skin disease illustrated through cases. Although simple treatments are often beneficial (e.g. use of emollients and topical steroids), many patients have complex disease and can present with more than one condition and therefore careful assessment and an individualised management approach is essential. Understanding of when to refer onwards to a vulval specialist service is important to optimise clinical outcomes. Clinical outcomes to consider for all patients with vulval skin disease should include: (i) a reduction in symptoms (e.g. less itch, fewer flare-ups) (ii) an improvement in function (e.g. sexual function, mobility); and (iii) increased confidence in self-management (e.g. management of flare-ups and self-examination).